Biotechonomy Framework for Bioenergy Use. (September 2016) - Blumberga, Dagnija; Muizniece, Indra; Blumberga, Andra; Baranenko, Denis
Abstract: In this paper the concept of biotechonomy is introduced, as well as the main differences between bioeconomy and biotechonomy are explained. Biotechonomy is based on development of innovative biotechonologies for creation of products with high added value. This has been done due to the fact that both terms mostly are used interchangeably. However, while bioeconomy is a rational and efficient utilization of bio-resources, biotechonomy is the utilization of bioresources by producing new value-added products that are demanded and therefore are competitive with already existing products in the market. Moreover, these value-added products are produced by using innovative biotechnology methods. The focus of this biotechonomical study is on biomass types that could be used in the production of bio-energy. Factors influencing the biotechonomy of bioenergy, as well as basic principles that have to be taken account by using bioresources have been evaluated and developed.